Influence of Blanching Temperature and Time on Quality of Minimally-Processed Mango during Frozen Preserva - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2020)
Mango (Mangifera indica L.) is one of the most important tropical fruits. It’s excellent source of nutrients, soluble fibres, bioactive compounds such as carotenoid, ascorbic acid and phenolic.  Mango pulp is very perishable with a short shelf life. It is very vulnerable to dehydration, discoloration, and decomposition. Objective of this study focused on the effectiveness of blanching (60oC in 4 minutes, 65oC in 3.5 minutes, 70oC in 3 minutes, 75oC in 2.5 minutes, 80oC in 2 minutes) to physico-chemical attributes of the minimally-processed mango during frozen storage for 6 months. Our results showed that minimally-processed mango should be blanched in hot water at 75oC for 2.5 minutes to maintain its shelf-life and physico-chemical characteristics during 6 months of frozen storage.Keywords: Mango; minimally-processed; blanching; physico-chemical; shelf-life; frozen storage